ANALISIS SEDIMENTASI DI MUARA SUNGAI ROKAN PROVINSI RIAU - Jannata Rahmad Putra; Rifardi Rifardi; Mubarak Mubarak (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
The research were conducted in River estuary of Rokan, Riau Province on Mei 2014. Sedimentation analysis were investigated by various method i.e, sedimen grain-size analysis, Total suspended solid analysis, mechanism of particle disseminated, river’s sediment transport analysis, longshore sediment transport analysis, coastline chance analysis and absolute sedimentation velocity. The research was aim to explained sedimentation procces covered mechanism of sediment transport and sedimentation rate, and then could be able to gave the solution for preventive study of River estuary of Rokan Sedimetation. The result of grain-size analysis showed that mean size were dominated by find sand, sorted by poorly sorted. The disseminated of sediment in deep water was tended to very fine skewed dan skin-deep was very coarse skewed. Mechanism of disseminated particle result when tide, find sand sediment was transport as 128,52 m to the south-east in 23,33 minute. On the contrary to the northwest as 88,10 m in 16 minute. Very find sand was transport as 82,59 m to the south-east in 15 minute at tide and on the contrary to the northwest as 67,12 m in 11,27 minute. Total Sediment Transport Formulae showed 137.023 m3/year of sediment transport was occurred, while longshore sediment transport was 33.616.808,53 m3/year at the River estuary of Rokan. The coastline chance showed addition of land at the estuary was 240.096.862,77 m2 , accretion was 280.492.425,46 m2, and abration was 27,935,195.86 m2. From sediment total calculation in a year comparing by 60 years accretion showed, the absoluted sedimentation velocity was 0,19 cm/year. It was low, so that concluded the contriction of estuary by accretion.